EFEKTIVITAS PIJAT OKSITOSIN TERHADAP PRODUKSI ASI DAN INVOLUTIO UTERI PADA IBU POST PARTUM HARI KE-0 DI PUSKESMAS JETIS 1 BANTUK TAHUN 2011 - Sidik, Nurul A.; Widyastuti, Yani; Purnamaningrum, Yuliasti Eka (Poltekkes Kemenkes Yogyakarta, 2012)
The Infant Mortality Rate in Indonesia by Demographic and Health Survey the year 2007 still high as 34/1000. The cause of the problem of infant modality associated with drinking milk, less milk can affect milk production, decreased milk production on the first day of the birth due to a lack of stimulation of the hormone prolactin and oxytocin affecting lactation. The decrease in baby sucking hormone stimulation can lower prolactin and oxytocin. The main cause of maternal death is postpartum hemorrhage. Bleeding due to retained products of conception may hinder the process involusia uteri. A technique carried out by massage techniques oxytocin. Objectives to the effectiveness of massage and oxytocin on milk production involution uteri on day 0 postpartum mothers at the Health Center Jetis I Bantul District. Methods: The True Experiment study types. The study design was posttest - only control group, sampling technique with non-probability Consecutive sampling The sample in the study of maternal postpartum days 0, amounting to 62 people. Where 31 people in the experimental group and 31 people in the control group. Bivariate analysis techniques using independent test samples t-test. The result there was difference production of milk in the postpartum mother day it to zero are massaged the oxytocin between the control and treatment groups be obtained t count of 5.72 with p-value = 0.000 thus the p-value <0.05 and massage oxytocin has a 3 times greater odds for the increase in production of milk compared with the control group. And there is no difference involusio uteri of postpartum mothers day to zero are massaged oxytocin between the control and treatment groups obtained t count for 0.99 p-values = 0.000 thus tho pvalue> 0.05.